2021
DOI: 10.14569/ijacsa.2021.0120836
|View full text |Cite
|
Sign up to set email alerts
|

Determine the Main Target Audience Characteristics in M-learning Applications in Saudi Arabian University Communities

Abstract: In the fourth economic revolution, which is based on digital transformation, the e-learning process represents one of the most important processes needed to deal with the revolution through increased skills and knowledge. Thus, the automation services in the e-learning field represent one of the most important and supportive means of transferring and disseminating knowledge to reach a diverse and wide segment. This study focuses on defining the parameters and characteristics of the target audience, who are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…The findings of this systematic research work further clearly show that PEOU has a significant impact on the acceptance of the technology, and this corresponded with research conducted by Alsmadi (2020), Chatti and Hadoussa (2021), and Badwelan and Bahaddad (2021). This means that the easier the system is, the greater its acceptance, and vice versa.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The findings of this systematic research work further clearly show that PEOU has a significant impact on the acceptance of the technology, and this corresponded with research conducted by Alsmadi (2020), Chatti and Hadoussa (2021), and Badwelan and Bahaddad (2021). This means that the easier the system is, the greater its acceptance, and vice versa.…”
Section: Discussionsupporting
confidence: 85%
“…And this indicated that technical support has a positive influence on the acceptance of the technology, and this corresponds with research conducted by Alsmadi (2020), Chatti andHadoussa (2021), Al-Mamary et al, (2021), and Badwelan and Bahaddad (2021). Students face technical problems and are unable to solve them.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…, 2018; Abdallah et al. , 2021; Alyoussef, 2021; Badwelan and Bahaddad, 2021; Al Rahmi et al. , 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Identifying these factors is crucial for learners, teachers, and m-learning developers. Hence, other factors such as students' acceptance should be taken into consideration to successfully adapt m-learning to higher education (Thomas et al, 2013;Al-Emran et al, 2018;Abdallah et al, 2021;Alyoussef, 2021;Badwelan and Bahaddad, 2021;Al Rahmi et al, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%